Through-glass interposer integrated high quality RF components (2014)
High quality and compact RF devices, using the half mode substrate integrated waveguide (HMSIW) architecture loaded with a complementary split ring resonator (CSRR), are implemented on a glass interposer layer, which therefore serves as an interconnection layer and as a host medium for integrated passive RF components. Compared with the silicon interposer approach, which suffers from large electrical conductivity and therefore substrate loss, the glass interposer has advantages of low substrate loss, allowing high quality interconnection and passive circuits, and low material and manufacturing costs. Corning fusion glass is selected as the substrate to realize the compact CSRR-loaded HMSIW resonators and bandpass filters (BPFs) working under the principle of evanescent wave amplification. Two and three pole bandpass filters are designed for broadband operation at 5.8 GHz. Thru glass vias (TGVs) are used to define the side-wall of the substrate integrated waveguiding structure. Surface micromachining techniques are used to fabricate the proposed devices. The variations of the external quality factor (Qe) of the resonator and the internal coupling coefficient (M) of the coupled resonators are studied for filter design. Operation of the filters at 5.8 GHz with a fractional bandwidth (FBW) of more than 10% for an in-band return loss of better than 20 dB and an low insertion loss of less than 1.35 dB has been obtained, which is not feasible with a usual Si interposer approach. Measurement results are presented from 2 to 10 GHz and show good agreement with simulated ones. © 2014 IEEE.